ASSAM MOVEMENT: ITS DEMOGRAPHIC CONTEXT AND CONSEQUENCES - Das, Nilakshi; Dowarah, Kuntala (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The organized groups of people united in order to achieve some concrete goals, which are commonly perceived by their various members, generally characterize social movements as uninstitutionalized collective action. The members are trying to bring about changes in society, politics or economics of the national state. A feeling of alienation, deprivation or inequality drives them to move away from it. However, it is important to point out that these movements are not simply mobilisers of resources but they also have a catalytic role in society's socio-political transformation. It is found that there are as many different analyses available in today's studies of social movements as there are diverse and complex movements within them. According to some scholars, social movements unfold itself in a cyclical fashion (both ideologically and socio-politically) and also that their emergence occurs almost in tandem with the larger socio-political crisis in a given society.